2005
DOI: 10.1194/jlr.m500389-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Altered lipoprotein subclass distribution and PAF-AH activity in subjects with generalized aggressive periodontitis

Abstract: In this study, we examined whether the documented increase of plasma triglycerides in patients with generalized aggressive periodontitis (GAgP) is associated with changes in lipoprotein subclass distribution and/or LDL-associated platelet-activating factor acetylhydrolase (PAF-AH) activity. Lipoprotein subclasses were analyzed in whole plasma samples using nuclear magnetic resonance methods. Compared with subjects without periodontitis (NP subjects; n ‫؍‬ 12), GAgP subjects (n ‫؍‬ 12) had higher plasma levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 67 publications
4
23
2
Order By: Relevance
“…Studies have shown that advanced HIV infection and severe periodontitis are associated with a high prevalence of sdLDL particles [5,6]. We have previously shown that patients with acute brucellosis and EBV infection have decreased mean LDL particle size [4,7].…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that advanced HIV infection and severe periodontitis are associated with a high prevalence of sdLDL particles [5,6]. We have previously shown that patients with acute brucellosis and EBV infection have decreased mean LDL particle size [4,7].…”
Section: Discussionmentioning
confidence: 97%
“…Advanced stages of human immunodefi ciency virus infection are associated with an atherogenic lipid profi le, including a high prevalence of sdLDL particles ( 32 ). Moreover, severe periodontitis is associated with an increase in sdLDL-C levels ( 2 ). But which could be the reasons for the increased sdLDL-C and consequently decreased LDL size during acute infection in the absence of increased TGs?…”
Section: Discussionmentioning
confidence: 99%
“…The effects of infl ammation on the distribution of LDL subclasses have been investigated ( 9,31 ). An increase in sdLDL particles in response to infection has been reported in some studies ( 2,32 ).…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Generalised aggressive PD is associated with the putative pathogens Pg and Aa 14. It is demonstrated that patients with generalised aggressive periodontitis have twice the concentration of sd-LDL compared with subjects without PD 15. This essentially means the concentration of ApoB is doubled.…”
Section: Pathogenesis Part 1: Serum Lipoprotein Concentrationmentioning
confidence: 95%